The Impact of Foreign Investment on The Chineese Companies’ Development - Ping Jia; Elena Kolganova (Communications of International Proceedings, 2021)
The paper is devoted to problems of Chinese companies’ foreign direct investments. Special attention is paid to the activity of Greenland Group. The company is focused on building a whole industrial chain of finance, implementation of the “big finance” development strategy, and active involvement in managing businesses including financial asset management, trust, investment banks, operation of small loan companies.
Keywords: Investment; Banking; Financial Assets; Real Estate.